2010
DOI: 10.1159/000314640
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Genetic, Physical, and Cytogenetic Maps for <i>Brassica rapa</i> Chromosome A7

Abstract: Bacterial artificial chromosome (BAC) contigs have been genetically mapped to the 10 linkage groups of Brassica rapa by BAC end sequences (BES). To integrate the genetic, physical, and cytogenetic maps, fluorescence in situ hybridization (FISH) was used to anchor the assembly of BAC contigs onto Brassica chromosomes using representative BACs. This BAC-FISH approach can be used to identify chromosome arms on separate mitotic metaphase chromosomes or to map multiple BACs to single long pachytene chromosomes. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 187 publications
0
16
0
Order By: Relevance
“…Among the crop species in the Brassicaceae, the B. rapa genetic, physical, and cytogenetic maps have begun to be integrated by BAC-FISH (Koo et al 2004;Lim et al 2005Lim et al , 2007Yang et al 2007;Kim et al 2009;Mun et al 2009;Xiong et al 2010). However, to our knowledge, a complete karyotype analysis that reliably distinguishes each chromosome in B. oleracea and B. napus has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the crop species in the Brassicaceae, the B. rapa genetic, physical, and cytogenetic maps have begun to be integrated by BAC-FISH (Koo et al 2004;Lim et al 2005Lim et al , 2007Yang et al 2007;Kim et al 2009;Mun et al 2009;Xiong et al 2010). However, to our knowledge, a complete karyotype analysis that reliably distinguishes each chromosome in B. oleracea and B. napus has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that an ancient chromosome rearrangement occurred between the two duplicated regions of C4B in either the A or C genomes after the diversification from a common ancestor. The future of plant molecular cytogenetics is promising in terms of both methods and applications (Kato et al 2005;Walling et al 2005;Lamb and Birchler 2006;Danilova and Birchler 2008;Guerra 2008;Pires and Hertweck 2008;Lysak et al 2010;Xiong et al 2010). The robust novel chromosomal painting technique developed here will assist the understanding of chromosome pairing, homoeologous recombination, and genome evolution in the genus Brassica and will facilitate new applied breeding technologies in this genus that rely upon identification of individual chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…For this, BAC fluorescence in situ hybridization (FISH) experiments were performed using some of the BAC clones identified by Xiong et al (2010), which specifically and simultaneously label pairs of homoeologous chromosomes/regions. We first focused on the A1-C1 pair of homoeologs (Figure 7), which are collinear along their entire length (Parkin et al, 2005).…”
Section: The Dynamics Of Class I Co Formation Is Different Between Thmentioning
confidence: 99%
“…We then extended our BAC FISH survey to three other pairs of chromosomes that share homoeology only along one of their arms, i.e., the long arms of A3/C3, the long arms of A7/C6, and the long arm of A10/short arm of C9 (Parkin et al, , 2005Xiong et al, 2010). Every pair showed a distinct and specific pattern at metaphase I (Supplemental Figure 13): A10 and C9 recombined together much more frequently in Darmor-bzh than in Yudal allohaploids (Table 3; P = 0.0095); A7 and C6 recombined together in the same proportion of PMCs in Darmor-bzh and Yudal allohaploids ( (Table 3; P = 0.1915).…”
Section: The Dynamics Of Class I Co Formation Is Different Between Thmentioning
confidence: 99%
“…One of them is FISH with bacterial artificial chromosome (BAC) clones selected from a BAC contig physical map (Tang et al 2009;Xiong et al 2010). Another attractive approach is to isolate chromosomes and use them as template for polymerase chain reaction (PCR) with primers specific for molecular markers.…”
Section: Introductionmentioning
confidence: 99%